2019
DOI: 10.18502/jad.v12i4.358
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Activity of Adult Mosquitoes (Diptera: Culicidae) in a Focus of Dirofilariasis and West Nile Infection in Northern Iran

Abstract: Background: Mosquito-borne arboviruses such as West Nile, dengue, Rift Valley fever, and Sindbis viruses and the nematode Dirofilaria are reported in Iran, but there is little information on the seasonal activity of their vectors in the country. We aimed to determine the seasonal activity of adult mosquitoes (Diptera: Culicidae) in a focus of diro­filariasis and West Nile infection in Guilan Province, northern Iran.  Methods: Collections were carried out using light traps in seven counties at least two t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 32 publications
4
11
0
Order By: Relevance
“…sacharovi that is absent or rarely found in this area. 21,32,56 Probably, other factors such as rice fields, temperature, and humidity, instead of altitude, influence the composition of the species in the region. More accurate interpretation of the altitudinal data of An.…”
Section: Anopheles Clavigermentioning
confidence: 99%
“…sacharovi that is absent or rarely found in this area. 21,32,56 Probably, other factors such as rice fields, temperature, and humidity, instead of altitude, influence the composition of the species in the region. More accurate interpretation of the altitudinal data of An.…”
Section: Anopheles Clavigermentioning
confidence: 99%
“…There is not much data about the seasonal activity of culicine mosquitoes, especially in adult stage, in Iran [29]. The highest activity peak of Cx.…”
Section: Discussionmentioning
confidence: 99%
“…maculipennis s.l. showed the highest peak of activity in the mid-July in Guilan [29] and July-August in Kalaleh County of Golestan Province [30], northern Iran. In neighboring Turkey, the species peaked in August and July-August [66,67].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study conducted in India, it was found that the serological element of WNV in domestic ducks is highly prevalent in areas where WNV human cases were reported, which urged the public health authorities to implement surveillance programs to prevent future outbreaks [44]. Mosquito serology studies are discussed in another article where samples were collected by a suction tube and flashlight; the result of this study indicated that one of the WNV strains was persistent during the winter period, and more research in this matter was suggested [45].…”
Section: Asiamentioning
confidence: 95%